FMF Is Associated With a Wide Spectrum of MHC Class I- and Allied SpA Disorders but Not With Classical MHC Class II-Associated Autoimmune Disease: Insights From a Large Cohort Study - Watad, Abdulla; Bragazzi, Nicola Luigi; Adawi, Mohammad; Shoenfeld, Yehuda; Comaneshter, Doron; Cohen, Arnon D.; McGonagle, Dennis; Amital, Howard (Frontiers in Immunology, 2019)
Objectives: To test the hypothesis that familial Mediterranean fever (FMF)-associated autoinflammation may exaggerate the tendency toward adaptive immunopathology or spondyloarthritis (SpA)-associated disorders including major histocompatibility complex (MHC) class I associated disorders but not classical MHC class II-associated disorders that exhibit transplacental autoimmunity including myasthenia gravis and pemphigus. Methods: Seven thousand seven hundred forty-seven FMF patients and 10,080 age- and sex-matched controls in the Clalit Health Services medical database were identified and compared in terms of prevalence of SpA-associated disorders. We also evaluated four classical and strong MHC class II-associated disorders, namely, pemphigus vulgaris, myasthenia gravis, sarcoidosis, and pernicious anemia, to ascertain whether such associations with SpA-spectrum disease were specific or merely reflected the non-specific consequences of innate immune system activation on driving divergent types of immunity. The diagnosis of FMF was based on the medical records and not genetically proven. Results: FMF showed a strong association with MHC class I-related diseases: odds ratio (OR) of 28.58 [95% confidence interval (95% CI), 6.93–117.87; p < 0.0001] for Behçet's disease, OR of 10.33 (95% CI, 4.09–26.09; p < 0.0001) for ankylosing spondylitis, and OR of 1.67 (95% CI, 1.19–2.33; p = 0.0029) for psoriasis. For weakly MHC class I-linked diseases, an OR of 3.76 (95% CI, 2.48–5.69; p < 0.0001) for Crohn's disease and OR of 2.64 (95% CI, 1.52–4.56; p = 0.0005) for ulcerative colitis were found. No association was found between FMF and the four MHC class II-associated autoimmune disorders. Conclusion: FMF patients are associated with increased risk of SpA-related disease diagnosis including MHC-I-opathies but not MHC-II-associated autoimmune diseases, suggesting that tissue-specific dysregulation of innate immunity share between FMF and SpA spectrum disorders may drive adaptive immune MHC class I-associated conditions.